Gender dan Pembangunan di Dunia Ketiga - Sukawarsini Djelantik (Jurnal Administrasi Publik, 2008)
The development process affects women and men differentially. The after effects of colonialism and the peripheral position of Third World countries in the world economy exacerbate the effects of sexual discrimination on women. The penetration of capitalism, leading to the modernization and restructuring of traditional economies often increases the disadvantages suffered by women as the modern sector takes over many of the economic activities, such as food processing and making of clothes, which had long been the means by which women supported themselves and their families. A majority of the new and better paid jobs go to men but the male income is less likely to be spent on the family. The paper discusses the role of women and development, as a strategic issue in most developing countries includes Indonesia and to increase understanding on the importance of gender mainstreaming program being implemented in government policies to increase women bargaining position.Keywords: women, gender, feminism, women in development, gender mainstreaming.